An Application to Robot Manipulator Joint Control by Using Fractional Order Approach - Copot, Cosmin (Journal of Applied Nonlinear Dynamics, 2026)
This paper presents the application of fractional-order control strategy for the velocity control of a manipulator robot joint. A wellknown approach for robot joint control is to use an independent controller for each joint axis with a nested structure: an outer loop which computes the desired joint velocity in order to minimize the position error; and an inner loop which ensures the required velocity of the joint. A fractional-order controller was designed, tested and implemented on a manipulator robot. The communication between the robot and the controller was established via the Robotics System Toolbox fromMatlab® and the ROS (Robot Operating System) platform. The experimental results indicate that the flexibilities of the fractional-order PI controller allows it to outperform the conventional integer-order PI controller.